TERRITORIAL PLANNING AND TOURISM IN THE RURAL JOINVILLE-SC - Walkowski, Marinês da Conceição; Oliveira, Mirtz Orige; Vieira, Vinicius Boneli; Loch, Carlos (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
The rural southern Brazil shows potential for tourism due to the significant scenic beauty, cultural riches and land structure based on small family farms whose economic viability of the activities demand variation so pluriativa. However, for this potential can be tapped is a need for systematic information and spatialized that allow the user to access and enjoy the rural destinations and equipment. In this direction lies the challenge for territorial planning, using GIS data when making decisions, seek the strengthening of Joinville city as tourist hub in its region.